2009
DOI: 10.1002/pssc.200880912
|View full text |Cite
|
Sign up to set email alerts
|

Polar and nonpolar HVPE GaN substrates: impact of doping on the structural, electrical and optical characteristics

Abstract: Polar and nonpolar bulk GaN substrates with low defect density and high structural and optical quality are demonstrated. The effect of doping by silicon, oxygen and iron within moderate doping levels on the properties of the polar GaN substrates was found uncompromised, as confirmed by high resolution X‐ray diffraction and low temperature photoluminescence spectroscopy. In contrast, the lattice parameters were affected significantly, which has to be considered in the subsequent homoepitaxial device growth. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The free electron concentration, n e , as determined by conventional Hall effect measurements at room temperature showed a nearly complete donor ionization, i. e. the n e scales closely with the Si concentration in an agreement with previous studies. 22 The Ga vacancy density was studied by positron annihilation spectroscopy (PAS). In all samples, no vacancy signal was detected which leads to the conclusion that the Ga vacancy density was below 1×10 15 cm -3 (detection limit of the PAS).…”
Section: A Sample Growth and Characterizationmentioning
confidence: 99%
“…The free electron concentration, n e , as determined by conventional Hall effect measurements at room temperature showed a nearly complete donor ionization, i. e. the n e scales closely with the Si concentration in an agreement with previous studies. 22 The Ga vacancy density was studied by positron annihilation spectroscopy (PAS). In all samples, no vacancy signal was detected which leads to the conclusion that the Ga vacancy density was below 1×10 15 cm -3 (detection limit of the PAS).…”
Section: A Sample Growth and Characterizationmentioning
confidence: 99%
“…The use of H 2 carrier gas and its effect on the efficacy of p-type doping with Mg is a point of controversy in the reports due to the formation of Mg-H complexes and the need for thermal annealing that is usually performed in situ directly after the growth. The semi-insulating type of HVPE-GaN was reported by using Fe compensating doping [12], [13], achieving free carrier concentration as low as 5 Â 10 13 cm À3 [13]. The optimization of the HVPE-GaN growth is impeded by the typical complications of crystal growth technology like the multidisciplinary nature and complex multiparameter character of the process.…”
Section: A Hydride Vapor Phase Epitaxymentioning
confidence: 99%
“…The development of substrates with both nonpolar and semipolar surfaces was initiated by utilizing foreign substrates, such as (1-102) sapphire or (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) SiC for a-plane GaN, (100) LiAlO 2 or (1-100) SiC for m-plane GaN, and (100) MgAl 2 O 4 for (10-11)-plane GaN, or (110) MgAl 2 O 4 for (10-13)-plane GaN [59]. The HVPE growth of thick layers GaN has also benefited from the ability for self-separation from some of the above substrates [60].…”
Section: Nonpolar and Semipolar Substrate Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…4 For example, in GaN crystals grown by the hydride (halide) vapour-phase epitaxy (HVPE) an unintentional n-type conductivity originates from the background doping by silicon and oxygen from the quartz elements of the reactor or from the process gases (Paskova et al, 2010). Fe compensating doping allows one to achieve semi-insulating properties of the layer in this growth method (Vaudo et al, 2003) with the the lowest free carrier concentration reported so far 5 · 10 13 cm −3 (Paskova et al, 2009). However, the performance parameters of AlGaN/GaN heterostructure field-effect transistor (HFET) structure formed by depositing a layer of AlGaN on a relatively thick semi-insulating GaN epitaxial layer are greatly improved by replacing a GaN epitaxial layer with a highly resistive AlN epitaxial layer in the device structure, in particularity, parasitic conduction in the GaN epilayer, leakage current through the GaN epilayer, and the channel electrons spillover into the GaN epilayer have been completely eliminated and the drain current collapse has been reduced (Fan et al, 2006).…”
mentioning
confidence: 99%